Fatores medicamentosos que influenciam na produção de leite materno - Patricia Amaral Vasconcellos; Mauricio Obal Colvero; Humberto Holmer Fiori (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Several factors may affect the production of breast milk - among them, the difficulty in breastfeeding per se, the reduction of oxytocin due to stress, and the use of medication. In this study, a systematic review of the subject has been made through the use of the following databases: PubMed, Scielo, and LILACS. OBJECTIVE: To evaluate the factors medicated that influence breas tmilk production. DISCUSSION: Medications such as galactagogues and lactation inhibitors interfere in the process - either increasing or decreasing the volume of milk produced by the mothers. CONCLUSÃO: On the other hand, medications like metoclopramide, sulpiride, and domperidone are galactagogues, that is, they increase milk production. Among the medications that may inhibit lactation, pseudoephedrine stands out. However, further studies are necessary to evaluate the actual safety of mothers use of medication while breastfeeding.